Fully automated synthesis of PET TSPO radioligands [11C]DAA1106 and [18F]FEDAA1106 - Wang, Min; Gao, Mingzhang; Zheng, Qi-Huang (Applied radiation and isotopes, 2012)
[11C]DAA1106 was prepared by O-[11C]methylation of DAA1123 with [11C]CH3OTf and NaH in CH3CN at 80°C and isolated by HPLC combined with SPE purification in 60–70% decay corrected radiochemical yield. [18F]FEDAA1106 was synthesized by the nucleophilic substitution of tosyloxy-FEDAA1106 in DMSO with K[18F]F/Kryptofix 2.2.2 at 140°C and isolated by HPLC combined with SPE purification in 30–60% decay corrected radiochemical yield. The specific activity for [11C]DAA1106 and [18F]FEDAA1106 was 370–740GBq/μmol and 37–222GBq/μmol at EOB, respectively. ► Fully automated syntheses of [11C]DAA1106 and [18F]FEDAA1106 have been developed. ► Simplified solid-phase extraction (SPE) method was employed in radiosynthesis. ► Syntheses of DAA1106, FEDAA1106 and their precursors have been improved.